Penerapan Prinsip Pengelolaan Lingkungan Hidup dalam Peraturan Perundang-Undangan Bidang Sumberdaya Alam (Kajian dari Perspektif Politik Pembangunan Hukum) - Efendi Efendi (Kanun Jurnal Ilmu Hukum, 2012)
ABSTRACT: This article explores principles that must be focused in managing the management of natural resources and legal politics that must be run to fulfill the implementation of the principles in managing it in the Act of Natural Resources. Sveral policies of law have been issued by the state both the Act of Environment and the Act of Natural Resources. From such rules, the principles and norm of management fair environment, democratic and sustainable has not been accommodated and integrated fully. To realize such principles and norms into several legal products, the state has done efforts in legal reform, either on the acts relating to matters or the act relating to making the rules.   The Implementation of Environmental Management Principle in The Act of Natural Resources (The Study on Legal Development of Politics Perspective)